An Exploration of Gender Stereotypes Based on Leader Idealisations in the New Zealand Hospitality Industry - Pan, Meichi (Auckland University of Technology, 2023)
Gender biases hinder women’s careers and indicate that women are not ideal leaders. Despite the positive changes currently taking place, these biases are persistent. Gender studies of the New Zealand hospitality industry are few in number, especially studies about gender and leadership; some previous studies have limitations (e.g., studies based on one country’s problems) that retain the gender norms instead of dealing with these norms. The research presented in this dissertation explored the factors influencing gender stereotypes in regard to leaders in the hospitality industry in New Zealand. Its aim was to obtain insights into these stereotypes and analyse the factors determining them. A literature review research approach was employed as the methodology to analyse the results of previous research. Based on this methodology, a semi-systematic review was used to collect secondary data from previous journal articles and theses. The data covered three aspects of the topic – social, organisational and individual – and compared current gender stereotypes influencing leader idealisation in the hospitality industry. The findings showed that global gendered stereotypes were reflected in New Zealand’s gender norms. The findings suggest that three factors informed gender stereotypes about leader idealisation: the belief in gender differences, the glass ceiling, and hospitality employees’ negative attitudes arising from gendered norms. These three factors interacted to influence the gender norms in New Zealand hospitality workplaces and global hospitality workplaces, and to inform the gender stereotypes that indicate women are not ideal leaders. These findings suggest that the glass ceiling’s existence is based on social gender differences and impacts individuals’ perceptions, including women’s lack of confidence, and men’s wish to retain their privileges. Current gendered leadership idealisations have developed from past gendered norms with some changes; currently, some show more benefits for women; however, gendered norms are persistent and some changes further inform the gendered stereotypes that hinder women’s careers.